Depression symptoms, communication and cooperation skills, and friendship: longitudinal associations in young Norwegian children - Krygsman, Amanda; Vaillancourt, Tracy; Janson, Harald; Idsoe, Thormod; Nærde, Ane (Frontiers in Child and Adolescent Psychiatry, 2024)
Introduction Symptoms of depression in early childhood have been linked to interpersonal difficulties, whereas friendships serve a protective function. Methods In the present study, we examined depression symptoms in preschool age (4 years) in relation to social skills (communication and cooperation), and friendships into early school age (Grades 1 and 2) in a large subsample (n = 943) of Norwegian children. Results The results indicated that preschool depression symptoms negatively predicted Grade 1 communication skills, which in turn predicted Grade 2 depression symptoms. This pathway suggests that communication skills may be a maintenance factor for depression symptoms in young children. In addition, preschool depression symptoms predicted lower Grade 1 cooperation skills, which in turn predicted lower Grade 2 communication skills, suggesting that preschool depression symptoms may begin a cascade of social skill problems that affect cooperation and communication skills into early school years. Best friendships were negatively related to depression symptoms in preschool and Grade 2. Discussion Given that preschool depression symptoms impact the development of social skills and friendships, it is important to attend to depression symptoms in early childhood.